Rancang Bangun Sistem Monitoring Patroli Lingkungan Kampus Menggunakan Near Field Communication Berbasis Android dan Web Application - Jullia Fatriana Putri; Ahmad Taqwa; Irma Salamah (SMATIKA JURNAL, 2021)
Campus security is a condition that shows that every campus community must feel safe and comfortable. The higher the security level of the campus environment, the lower the risk of loss due to loss of assets or damage to the campus environment. Therefore, a research entitled "Design a Campus Environmental Patrol Monitoring System Using Near Field Communication Android-Based and Web Application." This study uses the method Rapid Application Development (RAD). The results of the development of this monitoring system can facilitate the monitoring of security officers whether they have performed their duties properly and correctly by using technology Near Field Communication. By using the android application to perform the process scanning and the web application makes it easy to monitor the position of security officers using maps. To provide information in real-time,this research was distributed using the Whatsapp Gateway. The test results using Black-Box Testing from the construction of this patrol monitoring system are 100% valid. And the UAT test results are in the range of 60%-79% where the user states "agree" and has fulfilled the user's needs.